2013
DOI: 10.5713/ajas.2012.12619
|View full text |Cite
|
Sign up to set email alerts
|

Flavour Chemistry of Chicken Meat: A Review

Abstract: Flavour comprises mainly of taste and aroma and is involved in consumers’ meat-buying behavior and preferences. Chicken meat flavour is supposed to be affected by a number of ante- and post-mortem factors, including breed, diet, post-mortem ageing, method of cooking, etc. Additionally, chicken meat is more susceptible to quality deterioration mainly due to lipid oxidation with resulting off-flavours. Therefore, the intent of this paper is to highlight the mechanisms and chemical compounds responsible for chick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
178
0
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 239 publications
(193 citation statements)
references
References 58 publications
(112 reference statements)
4
178
0
11
Order By: Relevance
“…The adenosine triphosphate (ATP) degraded to AMP, IMP, inosine, hypoxanthine, and ribose after slaughtering and these compounds are related to meat flavor (Jayasena et al, 2013a;Kim et al, 2012c). IMP has a role as an umami taste enhancer and also It can be supportive evidence for the relationship between IMP contents and muscle composition since chicken breast meat is composed with 90% type IIB muscle fiber compared to thigh meat composed of type I muscle fiber (Jayasena et al, 2014) in accordance with Jaturasitha et al (2008).…”
Section: Nucleotide Contentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The adenosine triphosphate (ATP) degraded to AMP, IMP, inosine, hypoxanthine, and ribose after slaughtering and these compounds are related to meat flavor (Jayasena et al, 2013a;Kim et al, 2012c). IMP has a role as an umami taste enhancer and also It can be supportive evidence for the relationship between IMP contents and muscle composition since chicken breast meat is composed with 90% type IIB muscle fiber compared to thigh meat composed of type I muscle fiber (Jayasena et al, 2014) in accordance with Jaturasitha et al (2008).…”
Section: Nucleotide Contentsmentioning
confidence: 99%
“…The fatty acid composition has a strong relation with meat flavor as lipid breakdown products give an important contribution through their oxidation and cooking (Calkins and Hodgen, 2007;Jayasena et al, 2013a). Jayasena et al (2013b) suggested that lipid oxidation lead itself to desirable as well as undesirable flavor in meat and meat products.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…일반적으로 닭고기 의 풍미에는 유리아미노산, 핵산, 다양한 지방산 조성과 휘 발성 물질 등이 영향을 미치는 것으로 알려져 있으며 (Jayasena et al, 2013), 특히 재래닭은 일반 육계보다 콜라겐 함량이 높고, arachidonic acid와 IMP(inosine-5'-monophosphate)가 풍 부하여 독특한 조직감과 우수한 풍미를 가진다고 알려져 있 다 Jeon et al, 2010;Jung et al, 2011;안 동현과 박소연, 2002;이경행 등, 2012).…”
unclassified
“…While the influence of high hydrostatic pressure on the survival of many foodborne pathogens is relatively well known, there is still a lack of comprehensive data on survival of C. jejuni. Exploring the possibility of C. jejuni inactivation in poultry meat is particularly important considering the constantly increasing consumption of poultry meat (Jayasena et al 2013), as well the possibility of cross contamination, even after slaughter (Kruk et al 2014). The results of this study will help to establish the parameters necessary to ensure the reduction of C. jejuni to the consumer safety level, and thus, reduce human exposure to contaminated poultry meat and its products.…”
Section: Introductionmentioning
confidence: 94%